Alat tes psikologi konteks Indonesia: Tantangan psikologi di era MEA - Suwartono, Christiany (Konsorsium Psikologi Ilmiah Nusantara, 2016)
Currently, Indonesia is entering the era of the ASEAN Economic Community (AEC), a golden opportunity and a challenge to be able to identify the potential of the nation in order to become an important player in the ASEAN region and even the world. A solution to face this challenge is through the trustworthy and reliable psychological tests. Unfortunately in Indonesia, the realization becomes hard as the given attention and effort for the test development in the Indonesian context are little. The version of available tests are very far behind from the original version, in both content and standardization. In addition, the test questions have been leaked and relatively accessible to public. As the result, the scores obtained from these tests become questionable, mainly in terms of the validity. One of the efforts to renew the tests is through test adaptation. In order to ensure the validity of the test adaptation results, International Test Commission has issued guidance on the adaptation process of the test. The intention is for the adapted test to be as beneficial as its original version. The other effort is by making novel tests according to the context and needs on the practice area. Good cooperation between the different occupation should also be prioritized and strengthened in order to provide the availability of valid and reliable tests.